2017
DOI: 10.1021/acssuschemeng.7b00558
|View full text |Cite
|
Sign up to set email alerts
|

Facile Hydrothermally Synthesized a Novel CdS Nanoflower/Rutile-TiO2 Nanorod Heterojunction Photoanode Used for Photoelectrocatalytic Hydrogen Generation

Abstract: With the application of ethylenediamine (EDA) as a solvent, a template, and co-ordination agents, novel photoanode architecture of the cadmium sulfide (CdS) nanoflower (NF)/rutile(R)-TiO 2 nanorod (NR) heterojunction is successfully synthesized using a facile two-step hydrothermal process. The optimized CdS (medium concentration; MC) NF/R-TiO 2 NR heterojunction exhibited a greatly enhanced visible-light photoelectrochemical (PEC) performance, whereby the highest photocurrent density of 3.23 mA cm −2 at 0.1 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…It is notable that the UV–visible absorption spectra of CdS@TiO 2 presented a similar characteristic with CdS rather than TiO 2 , mainly because of the low content of TiO 2 , which demonstrated that CdS@TiO 2 heterostructure had been successfully constructed. Furthermore, the CdS@TiO 2 possesses a strong visible-light absorption band and shows an evident blue shift accompanied by an increasing loading amount of TiO 2 , which suggests that suitable TiO 2 content in CdS@TiO 2 composites is beneficial [ 26 ] and consistent with the TEM results. Therefore, a reasonably designed TiO 2 shell thickness is crucial for high performance photocatalytic materials.…”
Section: Resultssupporting
confidence: 59%
“…It is notable that the UV–visible absorption spectra of CdS@TiO 2 presented a similar characteristic with CdS rather than TiO 2 , mainly because of the low content of TiO 2 , which demonstrated that CdS@TiO 2 heterostructure had been successfully constructed. Furthermore, the CdS@TiO 2 possesses a strong visible-light absorption band and shows an evident blue shift accompanied by an increasing loading amount of TiO 2 , which suggests that suitable TiO 2 content in CdS@TiO 2 composites is beneficial [ 26 ] and consistent with the TEM results. Therefore, a reasonably designed TiO 2 shell thickness is crucial for high performance photocatalytic materials.…”
Section: Resultssupporting
confidence: 59%
“…Therefore, it is necessary to design and synthesize TiO 2 -based semiconductor composite photocatalyst with exposed highly reactive facets to broaden its optical light absorption range and accelerate the separation of photogenerated electrons and holes, thus improving the photocatalytic efficiency [ 8 , 9 ]. To extend the light absorption range of TiO 2 to the visible region, numerous efforts have been made to combine TiO 2 with other semiconductors, such as Fe 2 O 3 [ 10 ], CdS [ 11 ], Cu 2 O [ 12 ], Ag 3 PO 4 [ 13 ], WO 3 [ 14 ], ZnS [ 15 ], and Bi 2 S 3 [ 16 ]. Among various inorganic semiconductors, cadmium sulfide (CdS) is considered to be one of the best cocatalyst candidates because of its appropriate bandgap (2.4 eV), low price and appropriate band edge position for photocatalytic redox reaction [ 4 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The higher C dl implies more accessible active sites for the ReS 2 /Ni 3 S 2 heterostructure. , Additionally, the electrochemical impedance spectroscopy (EIS) is measured to investigate the charge transport ability of the electrode. As shown in Figure b, the ReS 2 /Ni 3 S 2 heterostructure exhibits a smaller R ct than those of the Ni 3 S 2 /NF and ReS 2 –Ni 3 S 2 composites, suggesting the fastest charge transport. , …”
Section: Resultsmentioning
confidence: 91%